ปัญหาของการบริหารงานแบบบูรณาการ : ศึกษากรณีอุตสาหกรรมท่องเที่ยวประเภทป่าในเขตอำเภอชะอำและหัวหิน - วิทวัส บูรณะ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The objectives of this research are to study as follows : 1.To indicate the problem of policy implementation on CEO administration which is operated between the neighboring area lot in different bureaucratic administration 2.To show the problem of Thai administration under CEO policy. In doing this study, actors in provincial level, such as bureaucrats, business people and staffs of local government in Cha Am and Hua-Hin districts will be focused The finding are as follows: The CEO provincial governor system is established to increase the authorities of the provincial governor in area of personnel, budget, and decision making. The results show that the operation officers have agreed with the policy but they consider that the policy is not successful in real operating. Local business people are not satisfied with the CEO administration because there is no difference between the former administration and the CEO administration. The purpose of the policy, integration, haven’t been operated both at cluster (group of provinces) level and at provincial level. The researcher suggests that provincial administration staffs as practitioners should have more understanding of the government policy on the CEO administration system.